Imagery about suicide in depression--"Flash-forwards"? - Holmes, E; Crane, C; Fennell, M; Williams, J (2007)
Suicide is a significant world health problem, with more deaths by suicide globally than by war. We need to better understand the cognitive processes underlying suicidal thinking for improved treatment development. Cognitive psychology indicates that mental imagery can be causal in determining future behavior, yet the occurrence of suicide-related imagery has not previously been investigated. Interviews with 15 depressed and formerly suicidal patients in remission found that all patients reported experiencing detailed mental imagery in addition to verbal thoughts when at their most despairing, for example images of making a future suicide attempt. A clinical measure of the severity of suicidal ideation was associated with both preoccupation with suicide-related imagery and perceived imagery realness. Echoing flashbacks in posttraumatic stress disorder, the current images appeared like "flash-forwards" to suicide. These results provide the first data to our knowledge on the existence of mental imagery in suicidality, opening a promising new avenue for research.